Audit Keamanan dan Manajemen Risiko pada e-Learning Universitas Sangga Buana - Sandy Sandy; Hanhan Hanafiah Solihin (Jurnal Manajemen Informatika (JAMIKA), 2021)
Universitas Sangga Buana is an educational institution that continues to develop the following technological advances by creating an e-learning system for students to facilitate distance learning. This system is relatively new and still being developed, allowing there are still many gaps that others can exploit, especially on the security side of the system. To reduce system security vulnerabilities and data loss risks, it is necessary to conduct an audit of the e-learning system at the Universitas Sangga Buana. The stages used to determine security system vulnerabilities and risk management in e-learning systems use the NIST framework and the Acunetix application as a system security testing tool. The final result of the e-learning system audit is that the e-learning system of the University of Sangga Buana is at a reasonable level with no high system vulnerabilities found and well-implemented risk management.